Kepemimpinan Sekolah: Antara Kewibawaan dan Kesejahteraan - Sahari Sahari (Institut Agama Islam Negeri (IAIN) Manado, 2017)
ABSTRACT Discussing about the school certainly will not be separated from leadership problems. Good and effective leadership can only be realized when executed in accordance with its duties and functions, namely as a driving force, determining the direction of school policy, which will determine how school goals and education are generally realized. The success of principals in performing their duties as leaders and managers of education is determined by several factors. Among these factors is dignity and welfare. Further explanations of welfare and dignity as well as their relationship to the principal’s leadership are discussed in length in this paper.Keywords: Leadership, welfare, dignity